A power line channel estimation mechanism based on compressed sensing - Yeshen HE; Kun LIANG (Dianxin kexue)
Through the analysis of power line channel characteristics,the corresponding mathematical model was established,the multipath channel characteristics of power line were studied.Combined with a novel compressed sensing and processing technology,a channel estimation method of power line based on compressed sensing was proposed.The transmission characteristics of power line channel were analyzed.Taking advantage of its sparse,only a small amount of noise and channel parameters needed to be collected,extracted and stored,which greatly reduced the digital signal processing module of data processing,and the storage hardware requirements and hardware costs were reduced.